Mr. Lincoln the life of Abraham Lincoln - Guelzo, Allen C.; The Teaching Company ([Chantilly, VA ] : The Teaching Company, 2005)
Professor Guelzo looks at Lincoln's life and legacy, from his youth and maturation into a successful lawyer through the evolution of his views on slavery to his presidency and triumphant management of emancipation and the restoration of the union
lecture 1. Young man Lincoln -- lecture 2. Whig meteor -- lecture 3. Lincoln, law, and politics -- lecture 4. The mind of Abraham Lincoln -- lecture 5. Lincoln and slavery -- lecture 6. The great debates -- lecture 7. Lincoln and liberty, too -- lecture 8. The uncertain president -- lecture 9. The emancipation moment -- lecture 10. Lincoln's triumph -- lecture 11. The president's sword -- lecture 12. The dream of Lincoln
Title from title screen
Lecturer: Allen C. Guelzo
Keywords: Lincoln, Abraham, -- 1809-1865; Lincoln, Abraham, -- 1809-1865 -- Political and social views; Presidents -- United States -- Biography